Climate Change Assessment On Drought In Sabah & Sarawak - Nah, Kian Kok (2020)
Drought is one of the costliest natural disasters that had been troubling human beings for untold years. There are 4 categories of drought such as the agricultural, meteorological, socioeconomic and the hydrological drought. A drought monitoring system had been introduced to monitor the drought characteristics in Sabah and Sarawak. The Standardized Precipitation Index (SPI) is being studied to investigate the drought characteristics in Sabah and Sarawak. The SPI is the only indicator that has been selected in this research due to the full data unavailability. Precipitation data for 1988-2017 (30 years) were acquired from Department of Irrigation and Drainage (DID). Since there were missing data, the four quadrant IDW method was applied for data repairing to get a complete data set, with the aid of the QGIS software. The SPI at timescales of 1-, 3- and 6-months had been utilised to determine the spatial distribution of drought characteristics, including Drought Frequency (DF), Mean Drought Duration (MDD), Mean Drought Severity (MDS), Mean Drought Intensity (MDI) and Mean Drought Peak (MDP). The temporal and spatial variation of drought characteristics in regions of Sabah and Sarawak were obtained and discussed. The droughts could be categorised as mild drought, moderate drought, severe drought and extreme drought. The SPI-1, SPI-3 and SPI-6 all showed multiple results of drought characteristics. For the temporal variation, the lowest, peak and the flow of drought occurrence in six 5-yr subperiods were examined in the research. In this study, the sub-periods of 1993- 1997 and 2008-2012 had the most occurrence of drought, whereas the subperiod 2003-2007 was with the lowest incidence of drought occurrence. Spatial variation was applied to analyse all the 9 regions in East Malaysia. For instance, the regions or areas that have shown relatively higher drought occurrence have been recorded. In this study, the Central (Region 3) and Eastern (Region 1) part of East Malaysia have constantly being facing the most drought occurrence. The results from the spatial and temporal variations were also linked to the factors of El Niño events and mountainous topography of East Malaysia to investigate the cost effect relationship.